Simultaneous atomic-resolution electron ptychography and Z-contrast imaging of light and heavy elements in complex nanostructures - H. Yang (Nature Portfolio, 2016)
The use of ptychography with electrons has been limited. Here, Yang et al. demonstrate that the combination of Z-contrast and phase imaging reveals the structure of complex nanomaterials. This practical tool can be used to solve the structure of a beam-sensitive carbon nanostructure at atomic-resolution.